Virtual Lab Demonstrations Improve Students’ Mastery of Basic Biology Laboratory Techniques - Grace A. Maldarelli (American Society for Microbiology, 2009)
Biology laboratory classes are designed to teach concepts and techniques through experiential learning. Students who have never performed a technique must be guided through the process, which is often difficult to standardize across multiple lab sections. Visual demonstration of laboratory procedures is a key element in teaching pedagogy. The main goals of the study were to create videos explaining and demonstrating a variety of lab techniques that would serve as teaching tools for undergraduate and graduate lab courses and to assess the impact of these videos on student learning. Demonstrations of individual laboratory procedures were videotaped and then edited with iMovie. Narration for the videos was edited with Audacity. Undergraduate students were surveyed anonymously prior to and following screening to assess the impact of the videos on student lab performance by completion of two Participant Perception Indicator surveys. A total of 203 and 171 students completed the pre- and posttesting surveys, respectively. Statistical analyses were performed to compare student perceptions of knowledge of, confidence in, and experience with the lab techniques before and after viewing the videos. Eleven demonstrations were recorded. Chi-square analysis revealed a significant increase in the number of students reporting increased knowledge of, confidence in, and experience with the lab techniques after viewing the videos. Incorporation of instructional videos as prelaboratory exercises has the potential to standardize techniques and to promote successful experimental outcomes.